Effect of Radiation on Employers in Radiology (X- rays, CT Scan and Magnetic Resonance Imaging )In Al-muthanna Province-Iraq - Hanaa Ali Aziz (Journal of Global Pharma Technology, 2018)
The aim of  this study was evaluated  the effect of radiation  on the hematological  parameter  of employers  in X- rays, CT scan  and  MRI units, during the period from October-2016 up to  March–2017. Fifty sample were examined  in the present study as well as twenty apparently  healthy  people   selected  as the control, their  ages  ranged  between  25-36 years  old. The samples were examined by using hematological tests. The study showed a significant   increase at (P<0.05) in Male, age groups (31-36) and blood group B. The  study  indicated  a  significant  decrease  at (P<0.05) in  red blood cells(RBC)  and  hemoglobin (HB)  compared  with  control   groups. Also, indicated a significant increase at (P<0.05) in white blood cells (WBC), Neutrophil, Monocyte and Lymphocyte compared with control   groups.                                                                                               Keywords: Hematological, Radiation, MRI, CT scan, Iraq.